2005
DOI: 10.1183/09031936.05.00058604
|View full text |Cite
|
Sign up to set email alerts
|

Nontuberculous mycobacteria in cystic fibrosis associated with allergic bronchopulmonary aspergillosis and steroid therapy

Abstract: Nontuberculous mycobacterial (NTM) infection, particularly due to Mycobacterium abscessus, is an emerging disease that can be relentlessly progressive, particularly in cystic fibrosis (CF) patients. The risk factors that were associated with this increasingly symptomatic infection in a group of CF patients were investigated.A total of 139 CF patients aged 2-52 yrs were reviewed. Sputum was cultured for NTM annually or whenever clinical deterioration was unexplained.In total, 12 patients (8.6%) had positive cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
100
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(106 citation statements)
references
References 29 publications
3
100
3
Order By: Relevance
“…6 Increases in MRSA, [7][8][9] A xylosoxidans, 8,10,11 and S maltophilia 8,9,12 have also been reported. The prevalence of nontuberculous mycobacteria (NTM) varies by age and by country, but has been increasing [13][14][15][16] particularly for Mycobacterium abscessus. 17,18 However, determining epidemiologic trends in CF microbiology can be challenging because of lack of reliable historical data for some pathogens; changes in reporting strategies; variations in sampling methods, microbiologic techniques, and culture frequency; and the patient population studied.…”
mentioning
confidence: 99%
“…6 Increases in MRSA, [7][8][9] A xylosoxidans, 8,10,11 and S maltophilia 8,9,12 have also been reported. The prevalence of nontuberculous mycobacteria (NTM) varies by age and by country, but has been increasing [13][14][15][16] particularly for Mycobacterium abscessus. 17,18 However, determining epidemiologic trends in CF microbiology can be challenging because of lack of reliable historical data for some pathogens; changes in reporting strategies; variations in sampling methods, microbiologic techniques, and culture frequency; and the patient population studied.…”
mentioning
confidence: 99%
“…Patients with chronic lung disease are also prone to Aspergillus colonisation and infection [3]. Cystic fibrosis (CF) and NTM infection may be associated with allergic bronchopulmonary aspergillosis (ABPA) and steroid therapy [4].…”
mentioning
confidence: 99%
“…To date, several ABPA patients in whom NTM was isolated have been reported (12)(13)(14)(15)(16). The isolation of NTM can indicate the presence of both infection and simple colonization.…”
Section: Discussionmentioning
confidence: 99%
“…The isolation of NTM can indicate the presence of both infection and simple colonization. Most previous reports differentiated NTM infection from simple colonization (13,16) according to the ATS/IDSA criteria (12). Mussaffi et al reported that six of 139 cystic fibrosis patients had ABPA, four of whom developed concomitant NTM infection following the diagnosis of ABPA (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation